Quaternary volcanism in the Yura Monogenetic Field near Arequipa city, southern Peru - Aguilar, Rigoberto; Arteaga, David; Manrique, Nélida; van Wyk de Vries, Benjamin; Cueva, Kevin; Taipe, Edu; Guillou, Hervé; Scao, Vincent (Frontiers in Earth Science, 2022)
Arequipa (Peru) is an area where volcanic activity has been persistent during the Quaternary. Studies carried out in this area have highlighted the emplacement of ignimbrite deposits, large volcanic clusters and stratovolcanoes. Monogenetic volcanism is also present, although poorly explored and studied. Due to its location over an ignimbrite plain and poor state of preservation, the only identified monogenetic cone in the Arequipa basin was the Nicholson volcano, while other monogenetic centers remained unknown. This lack of information about the recent volcanism can lead to inadequate definition of scenarios in a hazard assessment in the region. The present study has investigated monogenetic volcanism in the northwestern edge of the Arequipa basin based on geological survey, geochronology and geochemical data. Here, we report for the first time five small volcanic centers such as Yura Viejo, Ccapua, Uyupampa, El Chiral and Patacocha, which together with the Nicholson volcano form the Yura Monogenetic Field. Stratigraphic considerations and new 40Ar/39Ar ages allow us to place the eruptive activity in the Middle–Upper Pleistocene (c. 195–54 ka). Phreatomagmatic, Strombolian and effusive eruptions characterize the monogenetic activity of the field. As a result of these eruptions, small scoria cones, maars, and lava flows/coulées were generated. The eruptive products show ubiquitous olivine phenocryst-rich (<10 vol%) set in a fine pilotaxitic groundmass, suggesting rapid ascent of basaltic magmas to the surface controlled by the tectonic setting. The analyzed rocks lie in a narrow range of basaltic-andesite composition (50.9–55.6 wt% SiO2) being the most mafic Pleistocene - Recent volcanic products identified in the Arequipa basin, along with the least differentiated magmas from the nearby Chachani volcanic cluster. This work shows how monogenetic volcanism can occur contemporaneous and closely spaced to larger volcanic clusters and active stratovolcanoes. We hope the information provided here will contribute to improve the risk management by highlighting the scenario of monogenetic eruptions that should be considered in the hazard assessment.